Política y comercio en la Guatemala del siglo XVII - Webre, Stephen (1987)
A study of the merchant community seventeenth-century Santiago de Guatemala and y the various means through wich it strivde to influence Colonial policies, specifically regarding commercial taxation and imperial trade regulations.